Inflation in Colombia - Vallejo Zamudio, Luis Eudoro (Universidad Pedagógica y Tecnológica de Colombia, 2016)
In recent months, inflation has presented a significant increase. Since February 2015has been above the upper limit of the range set by the Colombian Central Bank,fixed between 2 and 4 percent. As it is known, inflation is the continuous and sustainedincrease of the general price level,which is one of the objectives of economic policyin any country. Hence, the monetary authority will always use the tools necessary to achieve the target set in the macroeconomic projections.